Transcriptional regulatory logic orchestrating lymphoid and myeloid cell fate decisions - Godini, Rasoul; Yan, Jingjing; Chopin, Michaël (Frontiers in Immunology, 2025)
IntroductionThe differentiation of hematopoietic stem cells (HSCs) into diverse blood and immune cells is a complex, highly hierarchical process characterized by a series of tightly regulated steps. It involves a sequence of intermediate oligo-potent progenitors making successive binary decisions. This process gradually narrows down lineage possibilities until a final fate is reached. This step-wise process is tightly controlled by transcription factors (TFs) and their associated regulome, ultimately resulting in the differentiation of both lymphoid and myeloid compartments.MethodsWe unravel the lineage-specific gene regulatory circuitry controlling the development of B cells, T cells, innate lymphoid cells (ILCs), and dendritic cells (DCs). We employ weighted gene co-expression network analysis to characterize gene modules associated with the lymphoid or myeloid cell fate, enabling the identification of lineage-restricted TFs based on their expression patterns.ResultsBy identifying TFs whose expression is subset-restricted or those with a broader expression in the hematopoietic compartment, we construct a regulatory logic that potentially controls the development of these key immune cells. Our results point to conserved regulatory elements between ILCs, natural killer cells, and DCs. This analysis unravels an intricate relationship between each cell type and how the expression of key TFs dictates lineage specificity. We particularly dissect the elements associated with conventional DCs and plasmacytoid DCs.DiscussionIn conclusion, our findings shed new light on regulatory mechanisms controlling blood cell development and offer a blueprint that can be leveraged to better understand the molecular mechanisms underpinning blood cell development.